THE FORMATION OF ADDED VALUE AS A WAY OF DEVELOPING OF UKRAINE’S ECONOMY - DVORNYK, Inna; STADNYK, Victoriya (Herald of Khmelnytskyi National University. Economic sciences, 2023)
In the conditions of martial law, the economy of Ukraine found itself in a difficult situation: an almost complete stop of business activity, a fuel crisis, a sharp drop in exports, a break in logistics chains, shelling of the energy infrastructure. Ensuring the operation of key sectors of the economy, booking employees of strategic enterprises, effective use of limited resources, and the creation of a green corridor for the supply of goods became an important task for the country. Based on the results of the analysis of macroeconomic indicators, it was determined that in 2022 the budget deficit increased by 2.56 times and amounted to 495 billion hryvnias, the inflation index was 26.6%, which reflects the existence of galloping inflation, the average unemployment rate in 2022 increased to 25– 26%, the ratio of the volume of public debt to GDP was 78.4%. To improve the economic situation, we see the growth of GDP - one of the most important indicators - as one of the main tasks. The way of its increase is the formation of added value, which is added in the process of production of goods to the cost of raw materials, materials, and fuel at each stage of the movement of goods from the producer to the consumer. The article graphically displays the chain of formation of added value as confirmation of its importance. It was studied that in 2022, imports exceeded exports by 47%, while the amount of exports, compared to 2021, decreased by 17.3%, and imports increased by 18.6%. Reasons: martial law, closing of sales markets. It was determined that the main export positions in Ukraine are occupied by grain crops, sunflower oil, seeds and fruits of oil crops. Thus, Ukraine in the world market, in the vast majority, occupies a raw material niche. That is, raw materials that remain in the country and cannot be exported are the basis for the formation of added value. As a result, Ukraine should move towards the greatest possible degree of self-reproduction.
Keywords: added value; gross domestic product; economy; budget deficit; public debt